2020
DOI: 10.1111/jfpp.15162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different drying methods on the quality and microstructure of fresh jujube crisp slices

Abstract: This study investigated the effects of different drying methods, including hot‐air drying (HD), freeze drying (FD), and pressure‐differential puffing drying (PPD), on the quality and microstructure of fresh jujube crisp slices. Our data confirmed that PPD has the best effect, followed by FD and HD. Crisps dried using FD had good color and the best rehydration rate, shrinkage volume rate, and apparent density. The color, rehydration, and hardness of fragile chips by PPD and FD were similar; jujube slice volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…In the process of SD, due to its special drying characteristics, the material presented a relatively regular small particle structure (Shi, Bai, et al, 2018). Wang et al (2020) mentioned that the choice of drying method for fruits and vegetables has an important influence on the quality and microstructure of the resulting products, which coincides with our study, hence, our study also requires in vivo and in vitro simulated digestion experiments in the future.…”
Section: Resultssupporting
confidence: 85%
“…In the process of SD, due to its special drying characteristics, the material presented a relatively regular small particle structure (Shi, Bai, et al, 2018). Wang et al (2020) mentioned that the choice of drying method for fruits and vegetables has an important influence on the quality and microstructure of the resulting products, which coincides with our study, hence, our study also requires in vivo and in vitro simulated digestion experiments in the future.…”
Section: Resultssupporting
confidence: 85%
“…In addition, moisture loss and heating cause pressure in the cellular structure of the food leading to shrinkage and changes in the microstructure . [18,33]…”
Section: Effect Of Different Drying Conditions On the Microstructure Of Purple Cabbagementioning
confidence: 99%
“…On the other hand, although ready-to-eat snacks offer considerable market potential, they are perceived as unhealthy products due to their high energetic value, their salt and fat content, and the presence of trans-saturated fatty acids. Some studies reported in the literature have tested the feasibility of different drying treatments to monitor the modifications in physicochemical parameters of vegetable-based chips such as potato [ 31 , 32 ], pumpkin [ 33 ], jujube [ 34 ], or apples [ 35 ]. However, the addition of natural antioxidant extracts based on agricultural byproducts as a natural ingredient has not been extensively reported.…”
Section: Introductionmentioning
confidence: 99%